OP15 Efficacy of ustekinumab for Ulcerative Colitis through 4 years: Final clinical and endoscopy outcomes from the UNIFI long-term extension. (30th January 2023) - Danese, S; Afif, W; Abreu, M; Sandborn, W; Miao, Y; Zhang, H; Panaccione, R; Hisamatsu, T; Scherl, E; Leong, R; Rowbotham, D; Arasaradnam, R; et al.
Abstract: Background: Ustekinumab (UST) is an interleukin12/23p40 antagonist approved for treatment of moderate to severe Ulcerative Colitis (UC). Here we report final clinical outcomes based on the Mayo score, including the endoscopy subscore, from the UNIFI long-term extension (LTE) study through 4 years of UST treatment. Methods: Overall, 523 intravenous UST induction responders were randomised to subcutaneous maintenance therapy: 175 placebo (PBO); 172 UST 90 mg every 12 weeks (q12w); 176 UST 90 mg q8w. A total of 284 UST patients (pts) completed week (wk)44 and continued treatment in the LTE; pts receiving PBO were discontinued after study unblinding. Starting at wk56, randomised pts with UC worsening could receive a dose adjustment: PBO to UST q8w, UST q12w to UST q8w, and UST q8w to UST q8w (sham adjustment). Outcomes based on the Mayo score (including endoscopy assessed by a local reader) were evaluated at the final efficacy visit (wk200); pts who had treatment failure (i.e., had ostomy or colectomy or discontinued UST due to lack of therapeutic effect or worsening UC) before wk200 were also included, and they were imputed as nonresponders. Clinical remission was defined as a Mayo score ≤2 points and no individual subscore >1; clinical response as a decrease in Mayo score of ≥30% and ≥3 points from induction baseline with either a decrease in rectal bleeding subscore of ≥1 from induction baseline or a rectal bleeding subscore of 0 or 1; modified Mayo score (without Physician's Global Assessment subscore) response as a decrease in modified Mayo score of ≥30% and ≥2 points from induction baseline with either a decrease in rectal bleeding subscore of ≥1 from induction baseline or a rectal bleeding subscore of 0 or 1; and endoscopic improvement as an endoscopy subscore of 0 or 1. Results: Among 205 pts who were randomised to UST at maintenance baseline and continued treatment in the LTE, who either had Mayo score data (including endoscopy) at wk200 or had experienced treatment failure, 58.0% were in clinical remission, 80.0% were in clinical response, 79.5% were in modified Mayo score response, and 67.3% showed endoscopic improvement (Figure 1). Using an alternative "as observed case" analysis (without imputation for treatment failures), among 171 randomised pts who continued UST treatment through LTE and had an endoscopy score at wk200, 69.6% were in clinical remission, 95.9% were in clinical response, 95.3% were in modified Mayo score response, and 80.7% showed endoscopic improvement. Conclusion: Among these pts with a history of moderate to severe UC who continued UST treatment, approximately 2/3 or more were in clinical remission, clinical response, and/or demonstrated endoscopic improvement at 4 years.